Women at war - Ritchie, Elspeth Cameron; Naclerio, Anne L. (Oxford University Press, 2015)
In the very first text of its kind, Women at War brings together all available information and experience on women's physical and mental health in one resource to enlighten the practitioners caring for them. Our U.S Department of Defense is approximately 15% women with over 300,000 women having deployed since September 11th, 2001. This book reviews the epidemiology, changes in policy and demographics of women in the services, the factors affecting their health and health care while serving in austere environments, issues related to reproductive and urogenital health and how health care provide.